Alternative translation initiation generates a novel isoform of insulin-degrading enzyme targeted to mitochondria - Malcolm A. Leissring; Wesley Farris; Xining Wu; Danos C. Christodoulou; Marcia C. Haigis; Leonard Guarente; Dennis J. Selkoe (2004)
IDE (insulin-degrading enzyme) is a widely expressed zinc-metallopeptidase that has been shown to regulate both cerebral amyloid β-peptide and plasma insulin levels in vivo. Genetic linkage and allelic association have been reported between the IDE gene locus and both late-onset Alzheimer's disease and Type II diabetes mellitus, suggesting that altered IDE function may contribute to some cases of these highly prevalent disorders. Despite the potentially great importance of this peptidase to health and disease, many fundamental aspects of IDE biology remain unresolved. Here we identify a previously undescribed mitochondrial isoform of IDE generated by translation at an in-frame initiation codon 123 nucleotides upstream of the canonical translation start site, which results in the addition of a 41-amino-acid N-terminal mitochondrial targeting sequence. Fusion of this sequence to the N-terminus of green fluorescent protein directed this normally cytosolic protein to mitochondria, and full-length IDE constructs containing this sequence were also directed to mitochondria, as revealed by immuno-electron microscopy. Endogenous IDE protein was detected in purified mitochondria, where it was protected from digestion by trypsin and migrated at a size consistent with the predicted removal of the N-terminal targeting sequence upon transport into the mitochondrion. Functionally, we provide evidence that IDE can degrade cleaved mitochondrial targeting sequences. Our results identify new mechanisms regulating the subcellular localization of IDE and suggest previously unrecognized roles for IDE within mitochondria.